Perkembangan Kurikulum di Indonesia: Adaptasi terhadap Perubahan Zaman dan Kebutuhan Masyarakat - Denda Ginanjar; Fokky Fuad; Mohamad Abduh; Bayu Bagus Mulyana; Ari Muhamad Rahman; Hani Nuraeni (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2025)
The curriculum serves as a guideline for the teaching and learning process in schools. In Indonesia, the curriculum continues to evolve in line with changes in time and societal needs. These changes aim to adapt to advancements in science and technology, address challenges within the education system, and achieve more effective learning outcomes. This research adopts a qualitative approach with a literature study method, drawing data from journal articles, books, research reports, and other documents. The findings illustrate the evolution of the national primary education curriculum from 1945 to the Merdeka Curriculum of 2022, depicting a lengthy journey of curriculum adaptation to Indonesia's educational dynamics. The implications of this research emphasize the importance of developing a curriculum that is responsive to both global and local developments, as well as the necessity for an adaptive education system to meet the needs of modern society.